Ex-vivo biomechanical evaluation of the application of a novel annulus closure device to closure of annulus fibrosus - Ying, Yijian; Cai, Kaiwen; Cai, Xiongxiong; Zhang, Kai; Qiu, Rongzhang; Hu, Hangtian; Jiang, Guoqiang; Luo, Kefeng (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To investigate the technical feasibility of applying a simple suture guide device to close the annulus fibrosus (AF) of the intervertebral discs (IVD). Methods 30 sheep functional discal units (FDUs) were obtained and subjected to mock discectomy. Mock sutures were performed using 3–0 non-absorbable sutures under a novel AF suture device following a suture procedure. The FDUs were compressed under axial loading at 1.8 mm/min and evaluated for Failure load (N). Results The failure loads of the hand stitching group (Group H) and suture device stitching group (Group S) were significantly higher than those of the control group (Group C) (p = 0.033; p < 0.001). Conclusion This study provides reasonable reasons to believe that the simple suture guide device described here is technically feasible for AF defect closure. It thus constitutes an encouraging proof of concept for the proposed device; however, it does not constitute a complete demonstration of the device’s feasibility in the clinical setting considering that the annulus closure operation is performed ex vivo on functional spinal units, as opposed to within an environment that mimics the clinical setting. To this end, confirmatory experiments will be conducted such as more multiaxial or dynamic mechanical testing, and notably performing the surgery on sheep models instead of on ex vivo functional spinal units.